Actinotaenium globosum (Bulnh.) Först. ex Comp. (=Cosmarium globosum Bulnh.) and Staurastrum avicula Bréb. in the plankton of the Wigry Lake. Materials for phycoflora of the Wigry National Park - Kowalski, Wojciech W. A.; Szymańska, Hanna (Annales Universitatis Paedagogicae Cracoviensis Studia Naturae, 2024)
The paper presents information on the occurrence of mesotrophic taxa of the order Desmidiales in the Wigry Lake (north-eastern Poland). The morphology of the cells and the photographic and drawing documentation made it possible to classify them into three taxonomic units, which are: Actinotaenium globosum (Bulnh.) Först. ex Comp., Staurastrum avicula Bréb. var. avicula Ralfs and S. avicula Bréb. var. exornatum Messik. – the last variety has not yet been recorded in the phycoflora of Polish. The size of the cells and the submicroscopic ornamentation of their walls as well as the features of the shape of the internal organisation of the protoplast are consistent with the data. The identified taxa occur in large numbers in the plankton of the bay and waters of the Wigry Lake.